The Hermeneutics of Husein Muhammad and Nasaruddin Umar As A Reformulation of the Problems on The Surah An-Nisa in Indonesia - Muhamad Irfan Zakaria; Ubaidillah Hasan; Siti Marpuah (Dialogia, 2022)
The unresolved gender problem is caused by a less critical interpretation. This article aims to find gender relations based on the thoughts of Husein Muhammad and Nasaruddin Umar. This study used a comparative method and a qualitative approach with three formulations of the problem; First, what are the views of Husein Muhammad and Nasaruddin Umar toward women? Second, what are the thoughts of the two figures toward the verse on the creation of women, women's social roles, and polygamy? Third, how is the actualization of the character's thoughts on women in Indonesia? This study found that women are human beings who are equal and balanced with men through their rights and obligations as human beings. On the other hand, the differences between men and women are biologically non-exchangeable, but these differences are not discriminatory, but a way to partner with each other, work together and complement each other in goodness. The most striking thing in the comparison of interpretations was in the concept of understanding the verse, and both of them make a classification and contextual theory to understand the gender verses. The significance of Husein Muhammad and Nasaruddin Umar's thoughts can be seen in the results of their interpretations that are friendly to women and gender so that they can form knowledge of gender interpretation and civilization that is more precise and equal.